Analysis Of The Factors Influencing Labor Migration From Rural Areas In Lolofitu Moi District To Urban Areas - Arisman Halawa; Syah Abadi Mendrofa (UNIVED Press, 2026)
This study analyzes the factors influencing labor migration from rural areas in Lolofitu Moi District to urban centers. Labor migration from villages to cities in Indonesia remains a prevalent socio-economic phenomenon driven by disparities in employment opportunities, infrastructure, and living standards between rural and urban regions. Using a qualitative approach, data were collected through interviews, observations, and document analysis involving key local stakeholders. The study identifies four main push factors from rural areas: limited employment, low agricultural income, inadequate infrastructure, and weak local economic development. Pull factors from urban areas include better job prospects, higher incomes, access to education and healthcare, and modern lifestyles. The findings highlight the significant role of economic conditions, socio-cultural influences, and environmental limitations in shaping migration decisions. While remittances from migrants positively impact household welfare in the village, the migration also leads to a shortage of productive labor, reduced agricultural activity, and weakened community participation. The study recommends targeted rural development policies, promotion of local entrepreneurship, and improved infrastructure to reduce migration pressure and ensure sustainable rural livelihoods